Cardiac disease in pregnancy - Nqayana, T (Clinics Cardive Publishing, 2008)
SUMMARY: This study was a retrospective review of patient charts of a relatively large number of patients with cardiac disease in pregnancy in a developing country. Ninety-five patients were evaluated; the majority (n = 36) were in the age group 21−25 years. Rheumatic heart disease was the commonest aetiology; eight women required balloon mitral valvuloplasty and one had a valve replacement at 32 weeks’ gestation. There were no maternal deaths but morbidity was high; 13 patients were admitted in cardiac failure, nine had atrial fibrillation and three required intensive-care management. There were 86 live births of the 97 deliveries.